2021
DOI: 10.1038/s41598-021-92609-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Hounsfield unit change correlates with dynamic CT perfusion better than 4DCT-based ventilation measures in a novel-swine model

Abstract: To analyze radiation induced changes in Hounsfield units and determine their correlation with changes in perfusion and ventilation. Additionally, to compare the post-RT changes in human subjects to those measured in a swine model used to quantify perfusion changes and validate their use as a preclinical model. A cohort of 5 Wisconsin Miniature Swine (WMS) were studied. Additionally, 19 human subjects were recruited as part of an IRB approved clinical trial studying functional avoidance radiation therapy for lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…These reductions in area under the curve represent an overall reduction in contrast observed in the vessel and a change in the numerator from Equation ( 2 ). This response to radiation has been reported previously in irradiated vasculature [ 24 ], where it was observed that in vasculature irradiated above 25 Gy, there appeared to be a leakage of contrast from the vasculature into the non-vessel parenchyma. The observation of reduced post-RT area under the curve in fed contours but not in not-fed contours suggests an indirect damage effect to the low or unirradiated tissues where there is leakage in the highly irradiated vessel preventing contrast (and more importantly blood) from reaching the branching vessels.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These reductions in area under the curve represent an overall reduction in contrast observed in the vessel and a change in the numerator from Equation ( 2 ). This response to radiation has been reported previously in irradiated vasculature [ 24 ], where it was observed that in vasculature irradiated above 25 Gy, there appeared to be a leakage of contrast from the vasculature into the non-vessel parenchyma. The observation of reduced post-RT area under the curve in fed contours but not in not-fed contours suggests an indirect damage effect to the low or unirradiated tissues where there is leakage in the highly irradiated vessel preventing contrast (and more importantly blood) from reaching the branching vessels.…”
Section: Discussionsupporting
confidence: 85%
“…The novelty of the swine model use in this work allows for more direct translation into human studies than previous animal models. Previous work has already established a strong correlation between the WMS and human radiation-induced lung density changes [ 24 ]. The WMS at the size used in this work had lungs that matched human adult lungs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational approaches have the advantages of allowing quantitative, continuous, objective and automated classification of radiological or functional lung damage. One of the most common approaches has been to use Hounsfield Unit (HU) density [ 31 , 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Palma et al [ 52 ] performed deformable image registration on the phase of the planning scan with the lung volume most similar to the 3-month follow-up CT images of patients treated with SABR.…”
Section: Discussionmentioning
confidence: 99%